DART model from a customer's perspective: An exploratory study in the hospitality industry of Greece - Solakis, Konstantinos; Peña-Vinces, Jesús C.; Lopéz-Bonilla, Jesús Manuel (My University, 2017)
The customers are an essential element for marketing decisions and became a factor decisive to develop collaborations with the company. The study examines the four building blocks of the interaction of the DART model (Dialogue, Access, Risk Assessment, Transparency) in the hospitality industry from the client's perception. This approach of the research is paramount, as value co-creation and DART model especially are based on a dialogical process between equal partners. That means that the principles of the four building blocks of interaction are equally applied to all the actors involved. This argument is amplified as the dividing line between producers and consumers is barely evident in the service-dominant logic. The exploratory study has been carried out at the Makedonia International Airport in Thessaloniki, Greece. Partial Least Squares (PLS) provides empirical support to conduct the exploratory study.
Keywords: DART model; S-D logic; Positive experience; Hospitality industry